Kode Vicious: Sanity vs. Invisible Markings: Tabs vs. spaces. - Neville-Neil, George V. (Communications of the ACM, 2020)
The article provides an answer to a question regarding computer coding, particularly restrictions surrounding tabs and spaces in source code.